THE USE OF DOWNWARD COMMUNICATION AT PT. HADJI KALLA (HOLDING) - Muhammad Fadhil Rusli; Fatimah Hidayahni Amin; Riny Jefri; Surya Anantama Sembiring (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2026)
This research aimed to find out the kinds of communication used in downward communication and its types employed in communication in Finance Division, PT. Hadji Kalla (Holding). It is a descriptive qualitative method. The data collection technique in this study was carried out using direct observation with video and audio recording, and interview questions in downward communication in the finance division. The subjects in this study were all employees in the Finance Division of PT. Hadji Kalla (Holding) which is one superior and two subordinates. Based on the results of direct observations conducted by researchers, the finance division managed and implemented the kinds of communication used, namely verbal and non-verbal communication. Superiors and subordinates at PT. Hadji kalla (Holding) uses verbal communication as a form of communication so that work goes well, while verbal communication is often used by superiors and subordinates, namely using simple sentences so that superiors and subordinates quickly understand information or task instructions. In addition Non-Verbal Communication is sign language, non-verbal communication within the scope of the office in the finance division and also greatly influences work communication between superiors and subordinates. It can be concluded that downward communication has an important role because it affects the performance of superiors and subordinates at work, with the results of this study showing that superiors and subordinates communicate using verbal and non-verbal communication as communication tools.